Influence of variable ultraviolet radiation and oil exposure duration on survival of red drum (Sciaenops ocellatus) larvae. (19th July 2018) - Bridges, Kristin N.; Krasnec, Michelle O.; Magnuson, Jason T.; Morris, Jeffrey M.; Gielazyn, Michel L.; Chavez, J. Ruben; Roberts, Aaron P.
Abstract: The toxicity of some polycyclic aromatic hydrocarbons (PAHs) increases with ultraviolet (UV) radiation. The intensity of UV radiation varies within aquatic ecosystems, potentially providing reprieves during which tissue repair may occur. Transient/short‐term PAH exposure prior to UV exposure may initiate metabolism/clearance, potentially affecting outcomes. Larval Sciaenops ocellatus were exposed to oil and UV radiation, using either variable photoperiods or pre‐UV oil exposure durations. Shorter PAH exposures exhibited greater toxicity, as did exposure to shorter photoperiods. Environ Toxicol Chem 2018;37:2372–2379. © 2018 SETAC